Pengembangan Kreativitas dan Berpikir Kritis pada Anak Usia Dini melalui metode pembelajaran berbasis STEAM dan Loosepart - Murgiyanti Murgiyanti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
STEAM is a new innovation in the era of disruption in the world of education. which is an integrative thematic learning, scientific approach and technology-based, STEAM Method is a unit of learning to improve critical and creative thinking skills that can be carried out by all educational fields including early childhood education, and this STEAM learning method uses loose-based media parts which are used to stimulate children’s creativity. The purpose of this study is to develop the learning process using STEAM and loose part based learning methods. And to increase creativity and critical thinking in children is characterized by children able to solve problems and be able to make connections with the surrounding environment. Using a loose part based STEAM learning method that is able to develop creativity and critical thinking of children. Children’s creativity can be seen from how to play, explore and have creative thinking skills and fluent, critical thinking skills that we can see in analyzing a problem, can explore in detail and systematically